Assessing the efficacy of group model building workshops in an applied setting through purposive text analysis. (19th August 2020) - Valcourt, Nicholas; Walters, Jeffrey; Javernick‐Will, Amy; Linden, Karl
Abstract: Group model building (GMB) approaches have been shown to improve participants' understanding of complexity by shifting and aligning individuals' mental models of the interconnections within complex systems. However, reviews of GMB literature have identified knowledge gaps for assessing the efficacy of GMB activities. To address these gaps, these studies recommend assessing multiple cases, shifting from controlled to applied settings, and reporting on objective measures. We address each of these items by comparing the outputs of multiple community‐based GMB workshops to participants' mental models elicited through pre‐workshop interviews. Using purposive text analysis, we developed causal loop diagrams for comparison to a group workshop model. Through a quantitative analysis, we find that individuals convened in GMB workshops have greater alignment on factors, causal links, and feedback. We believe these contributions can help other GMB practitioners better assess the efficacy of their activities with more rigor and detail. © 2020 System Dynamics Society